Parametric Study of a Turbofan Engine with an Auxiliary High-Pressure Bypass - Sharanabasaweshwara A. Asundi; Syed Firasat Ali (International Journal of Turbomachinery, Propulsion and Power, 2019)
A parametric study of a novel turbofan engine with an auxiliary high-pressure bypass (AHPB) is presented. The underlying motivation for the study was to introduce and explore a configuration of a turbofan engine which could facilitate clean secondary burning of fuel at a higher temperature than conventionally realized. The study was also motivated by the developments in engineering materials for high-temperature applications and the potential utility of these developments. The parametric study is presented in two phases. Phase I presents a schematic of the turbofan engine with AHPB and the mathematics of the performance parameters at various stations. The proposed engine is hypothesized to consist of three streams—core stream, low-pressure bypass (LPB) stream, and the AHPB or, simply, the high-pressure bypass (HPB) stream. Phase II delves into the performance simulation and the analysis of the results in an ideal set-up. The simulation and results are presented for performance analysis when (i) maximizing engine thrust while varying the LPB and AHPB ratios, and (ii) varying the AHPB ratio while maintaining the LPB ratio constant. The results demonstrate the variations in performance of the engine and a basis for examining its potential utility for practical applications.